2022
DOI: 10.1002/fld.5101
|View full text |Cite
|
Sign up to set email alerts
|

Mesh‐free model for Hopf's bifurcation points in incompressible fluid flows problems

Abstract: In this article, a new numerical model is proposed to detect numerically the Hopf bifurcation point of incompressible fluid flows problems. The concept of this model consists to propose a Hopf bifurcation indicator which is solved by a high order mesh free algorithm (HO‐MFA) using the moving least squares (MLS) approximation. This numerical model is based on a strong formulation of Navier–Stokes equations. This procedure allowed us to recover the results of the literature in 3D$$ 3D $$ using only a 2D$$ 2D $$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The third part concerns a flow around a square obstacle. The literature survey of the experimental and numerical works carried out on flow around obstacle indicates that limited studies are reported on cylindrical objects 10,13,28,29 . Motivated by this fact, the objective of this part consists to investigate the streamlines for the flow around a square cylindrical obstacle at several values of Reynolds number.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The third part concerns a flow around a square obstacle. The literature survey of the experimental and numerical works carried out on flow around obstacle indicates that limited studies are reported on cylindrical objects 10,13,28,29 . Motivated by this fact, the objective of this part consists to investigate the streamlines for the flow around a square cylindrical obstacle at several values of Reynolds number.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Then the proposed mesh‐free approach was also coupled with the homopic technique to study the compressible flows using a dimensional analysis 12 . In the context of dynamic flow, these approaches have been improved by a Hopf bifurcation study for an incompressible flow in Reference 13. Trias et al 36 investigated a turbulent flow around a square cylinder for a Reynolds number of 22,000.…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 3 more Smart Citations